2005
DOI: 10.1016/j.jacc.2004.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Stent underexpansion and residual reference segment stenosis are related to stent thrombosis after sirolimus-eluting stent implantation

Abstract: Stent underexpansion and residual reference segment stenosis are associated with stent thrombosis after successful SES implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 696 publications
(142 citation statements)
references
References 15 publications
5
127
1
Order By: Relevance
“…Previous reports showed that stent thrombosis may be associated with stent underexpansion,28, 29 smaller lumens, and more dissections,28, 30 but not with ASM28, 29 or tissue protrusion 28. In the current study, the final minimum stent area measured 6.3 (6.2–6.3) mm 2 (least‐squares means, 95% CI) and was numerically larger in lesions with ASM with few stents meeting standard criteria for underexpansion.…”
Section: Discussionsupporting
confidence: 43%
“…Previous reports showed that stent thrombosis may be associated with stent underexpansion,28, 29 smaller lumens, and more dissections,28, 30 but not with ASM28, 29 or tissue protrusion 28. In the current study, the final minimum stent area measured 6.3 (6.2–6.3) mm 2 (least‐squares means, 95% CI) and was numerically larger in lesions with ASM with few stents meeting standard criteria for underexpansion.…”
Section: Discussionsupporting
confidence: 43%
“…days) ST after bare metal stent (BMS) 9 and DES implantation 10 found stent underexpansion and residual stenoses as predisposing factors. However, no study examined structural differences in stented vessel segments in patients with very late ST (Ͼ1 year) after DES implantation.…”
Section: Editorial P 2379 Clinical Perspective P 2434mentioning
confidence: 99%
“…9,13 In a recent study of 21 patients with documented SES thrombosis occurring an average of 14 days after the index procedure, Fujii and colleagues 10 identified stent underexpansion and a residual reference segment stenosis as predictors of early ST. In the present study, 4 very late ST patients also had evidence of stent underexpansion, which was related to severely calcified lesions with a calcium arc of 360°.…”
Section: Other Ultrasonic Predictors Of Stmentioning
confidence: 99%
“…34,35 Intravascular ultrasound in 15 patients with ST compared with 45 control subjects revealed smaller minimal stent area (4.3Ϯ1.6 versus 6.2Ϯ1.9 mm 2 ; PϽ0.001), reduced stent expansion (65Ϯ18% versus 85Ϯ14%; PϽ0.001), and residual edge stenosis (67% versus 9%; PϽ0.001) to be more common in the ST patients than the control subjects. 56 …”
Section: Risk Factors Of Stmentioning
confidence: 99%